Pengembangan Media Kotak Si Bolang Materi Muatan IPA dalam Meningkatkan Hasil Belajar Kelas 1 MI - Eli Mufidah; Alimatus Sa’diyah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
The problem in this study is how to develop learning media for the box media, the material for the content of IPA, namely the material for grouping living and inanimate objects in order to improve the learning outcomes of class 1 students in MI MANSYAUL HUDA in each domain. The purpose of this study was to develop a valid, effective and practical learning media for the box media of living and inanimate objects. This research is R&D according to Borg and Gall. Data sources were obtained from 2 individual students, 6 small group students and 12 large group students. Validation of development research involves learning validators, mat erial validators, design validators, language validators and learning practitioners. The results of the research on the development of Si Bolang box media met the attractive criteria with the results of the material expert's test reaching an eligibility level of 84.6%, learning experts reaching 82.5%, design experts reaching 75%, linguists reaching 85%, learning practitioners experts, and the results Student learning in each domain has increased as seen from the average value of the Pre-test and Post-test scores, namely the cognitive learning outcomes of 73.75 to 83 The average number of learning outcomes in the affective domain is 71.25 to 84.9. The average number of learning outcomes in the psychomotor domain was 70.8 to 82.1. This shows that the product developed has an attractive eligibility level because the concepts are in accordance with the characteristics of children, so this media is suitable for use in learning.